Update Diagnosis dan Tatalaksana Meningitis Tuberkulosa Anak - Elvina, Fadhilah; Dimyati, Yazid; Saing, Johanes H.; Amelia, Fereza (Majalah Kedokteran Nusantara The Journal Of Medical School, 2017)
Tuberculous meningitis is the most devastating manifestation of pediatric tuberculosis (TB). Nowadays with the increase resistancy of M. tuberculosis, delay of antituberculosis administration and increase of HIV patient, morbidity and mortality of patient with tuberculosis are also increased. Tuberculous meningitis is diagnosed by clinical or laboratory findings. Recently, WHO develop Xpert as diagnostic tools, IGRA, NAATs, PCR, and any other tools help to diagnosed TB. Management with antituberculous drugs, antiinflammation and management of complication such as hydrocephalus.Keyword : tuberculous meningitis, diagnosis, management